2018
DOI: 10.31436/imjm.v17i2.990
|View full text |Cite
|
Sign up to set email alerts
|

Suggested Insulin Regimen for Pregnant Women with Diabetes Who Wish To Fast in Ramadan

Abstract: Introduction: Pregnant women are among those who are exempted from Ramadan fasting. Despite that, many pregnant women had chosen to fast despite understanding the risk of complications especially hypoglycaemia. In Hospital USM (HUSM), an insulin regime for pregnant women who wish to fast was designed based on expert opinion of obstetricians, but its safety and efficacy are yet to be determined. Objective: To determine the safety and efficacy of the formulated insulin regime using subcutaneous Actrapid® and Ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Healthcare providers are required to understand the religious beliefs of Muslim pregnant women and design the standard guideline about managing lifestyle changes of RF during pregnancy. Despite understanding the risk of complications, especially hypoglycemia, Yahaya et al [46] suggested an insulin regimen for pregnant women with diabetes who wish to fast in Ramadan. The total daily dose of insulin requirement BR was divided into 3 parts; ⅔ for Iftar (sunset meal) and ⅓ for Suhoor (pre-dawn meal).…”
Section: Antenatal Care During Ramadanmentioning
confidence: 99%
“…Healthcare providers are required to understand the religious beliefs of Muslim pregnant women and design the standard guideline about managing lifestyle changes of RF during pregnancy. Despite understanding the risk of complications, especially hypoglycemia, Yahaya et al [46] suggested an insulin regimen for pregnant women with diabetes who wish to fast in Ramadan. The total daily dose of insulin requirement BR was divided into 3 parts; ⅔ for Iftar (sunset meal) and ⅓ for Suhoor (pre-dawn meal).…”
Section: Antenatal Care During Ramadanmentioning
confidence: 99%